(untitled) (Proceedings of the International Conference on Social Sciences, 2024)
Child harassment is a severe problem affecting many children in Sri Lankan society. Child abuse can have a significant Impact on the mental and emotional health of the victim, with depression being one of the most common side effects. The aim of this study was to examine the impact of child harassment on depression and to identify the factors associated with depression among victims of child harassment between January 2023 and June 2023 a total of 80 patients attend Kalutara District Hospital psychiatric clinic a depressive symptoms were exhibited between the age of 14 – 18 years 22 children were used as the research sample exploratory findings on child abuse and depression were possible in those who reported child abuse, despite medical literature served as their primary source. Result indicated that the prevalence of depression was significantly higher among individuals who reported experience in child harassment compared to those who also reported harassment severity and frequency as factors the importance of depression in the victims. The study also found that social support played a protective role in reducing the negative impact of child harassment on depression. The findings of this study provide important insight into the long - term effects of child harassment on mental health and highlight the need for early victim identification and intervention emphasize. The study also highlights the importance of social support in preventing and reducing the negative impact of child harassment on mental health.